Risk factors associated with prolonged neonatal intensive care unit stay after threatened late preterm birth. (3rd April 2021) - Battarbee, Ashley N.; Glover, Angelica V.; Vladutiu, Catherine J.; Gyamfi-Bannerman, Cynthia; Aliaga, Sofia; Manuck, Tracy A.; Boggess, Kim A.
Abstract: Objective: To identify risk factors associated with neonatal intermediate or intensive care unit (NICU) stay ≥3 days among women with threatened late preterm birth (PTB). Study design: Secondary analysis of women with nonanomalous, singleton gestations enrolled in multicenter trial of betamethasone versus placebo for late PTB. Maternal and obstetric characteristics at time of presentation with threatened PTB were compared between those with and without NICU stay ≥3 days. Multivariable logistic regression identified risk factors for NICU stay ≥3 days. Result: Of 2795 eligible mother-neonate dyads, 962 (34%) had NICU stay ≥3 days. Gestational age and fetal growth restriction as the reason for threatened PTB had the strongest association with NICU stay ≥3 days in the final model (AUC 0.76). Conclusion: Maternal and obstetric characteristics at the time of admission for threatened late PTB should be considered when counseling patients about the probability of NICU stay ≥3 days.